Estimation of pupil size using a digital camera - Avelino L. Zapanta Jr., MD; Jerome S. Sarmiento, MD; Carlos Alberto, MD; Monserat A. Zapanta, MD (Philippine Journal of Ophthalmology)
Purpose: To compare pupil-size determination using a digital camera with the Rosenbaum-pupil-comparison and the millimeter-ruler methods.